Dual Responses of Fluorescence and Circular Dichroism for Antibiotics by a Cationic Cage in Water - Dong, Yunhong; Cheng, Lin; Duan, Yanjuan; Xu, Huiru; Dong, Ruonan; Guo, Baolin; Cao, Liping (Synlett, 2023)
A tetraphenylethene (TPE)-based cationic cage (1) can form a 1:2 host–guest complex with antibiotics in water and imparts dual responses of fluorescence and circular dichroism (CD) to antibiotics based on the fluorescence and adaptive chiral conformation of the TPE units. Moreover, the host–guest complexes 1⊃(antibiotic)2 exhibited good antibacterial activity.
Keywords: chiral response; host–guest recognition; tetraphenylethene-based cationic cage; antibiotics; antibacterial activity